¿CONDICIONAN EL GÉNERO Y LA EDAD EL NIVEL DE COMPETENCIA DIGITAL? UN ESTUDIO CON ESTUDIANTES UNIVERSITARIOS - Dr. Marcos CABEZAS GONZÁLEZ,Dra. Sonia CASILLAS MARTÍN,Dra. Manuela SANCHES-FERREIRA,Dr. Fernando Luís TEIXEIRA DIOGO (Fonseca, Journal of Communication, 2023)
The characteristics of Information and Communication Technologies (ICT) and their implementation at the global level have led to significant changes in different areas, especially institutional ones. This article presents the results of a research study whose purpose was to learn the level of digital competence of university students of education and to verify whether the variables of gender and age have any influence on it